The Meaning of Ahzab in the Quran: A Contextual Analysis of History and Its Application in Islamic Ethics - Muhammad Youssef Al Deek (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to clarify the meaning of the term Ahzab in the Qur’an and to examine its appropriate application within Islamic ethical and socio-political discourse. The research seeks to provide a precise linguistic and terminological understanding of Ahzab, while distinguishing its Qur’anic usage from contemporary political interpretations that often lead to conceptual misuse. Theoretical framework: The theoretical framework is grounded in Qur’anic semantics and classical Islamic scholarship, emphasizing contextual interpretation (siyāq and asbāb al-nuzūl) as essential tools for understanding key religious terms. Literature review: The literature review draws upon classical Qur’anic exegesis, authoritative Arabic dictionaries, and relevant contemporary studies to trace the historical, linguistic, and exegetical dimensions of Ahzab and related terms such as Hizbullah. Previous studies reveal a gap between traditional interpretations and modern political appropriations of Qur’anic terminology, which this research seeks to address. Methods: Methodologically, the study employs a qualitative inductive approach by identifying and analyzing all occurrences of the term Ahzab in the Qur’an. This approach is supported by descriptive and deductive methods, with systematic references to classical tafsir works and lexicographical sources to ensure textual accuracy and contextual consistency. Results: The findings demonstrate that Ahzab in the Qur’an consistently refers to groups or coalitions that oppose divine truth and prophetic missions, rather than neutral or legitimate political entities. Furthermore, the study confirms that Hizbullah does not denote a specific political party but signifies individuals and communities committed to faith, obedience, and moral integrity. Implications: The implications of this research highlight the ethical responsibility of interpreting Qur’anic terminology accurately, cautioning against its instrumentalization for political justification or social oppression. Novelty: The novelty of this study lies in its focused contextual and linguistic analysis of Ahzab, offering a corrective framework for contemporary discourse and contributing to a more ethical and textually grounded understanding of Qur’anic concepts.